MOTIVASI DAN KINERJA PEGAWAI NEGERI SIPIL DI KECAMATAN PAJAR BULAN - Ruaman Yudianto; Deki Fujiansyah (Equivalent : Journal of Economic, Accounting and Management, 2023)
This study aims to examine and analyze the motivation and performance of Civil Servants in the Pajar Bulan District. The results showed that the motivation given to employees in Pajar Bulan Subdistrict, Lahat Regency influenced employee performance such as individuals, organizations, and psychology. The coefficient value of 0.197 is relatively small but has a positive influence on the performance of Civil Servants in Pajar Bulan District, Lahat Regency. The internal motivation of each Civil Servant in the Pajar Bulan Subdistrict, Lahat Regency is greater than the given External Motivation. To improve the motivation and performance of sub-district employees, researchers suggest giving more tasks and delegation of authority to further increase the internal motivation of each employee. It is better if the superior understand the individual employees better to find out what kind of motivation should be given. Provide awards, greater achievement opportunities with agencies, and provide promotions to employees who have good work performance. Abstrak Penelitian ini bertujuan untuk mengkaji dan menganalisis motivasi dan kinerja Pegawai Negeri Sipil di Kecamatan Pajar Bulan. Hasil penelitian menunjukkan bahwa motivasi yang diberikan kepada pegawai di Kecamatan Pajar Bulan Kabupaten Lahat berpengaruh terhadap kinerja pegawai seperti individu, organisasi, dan psikologi. Nilai koefisien sebesar 0,197 relatif kecil namun berpengaruh positif terhadap kinerja Pegawai Negeri Sipil di Kecamatan Pajar Bulan Kabupaten Lahat. Motivasi internal masing-masing Pegawai Negeri Sipil di Kecamatan Pajar Bulan Kabupaten Lahat lebih besar dari Motivasi Eksternal yang diberikan. Untuk meningkatkan motivasi dan kinerja pegawai kecamatan, peneliti menyarankan untuk lebih banyak memberikan tugas dan pendelegasian wewenang agar lebih meningkatkan motivasi internal masing-masing pegawai. Sebaiknya atasan lebih memahami individu karyawan untuk mengetahui motivasi seperti apa yang harus diberikan. Memberikan penghargaan, kesempatan berprestasi yang lebih besar dengan instansi, dan memberikan promosi kepada pegawai yang memiliki prestasi kerja yang baik.